Mechanism of Cordyceps sinensis and its Extracts in the Treatment of Diabetic Kidney Disease: A Review - Liu, Wu; Gao, Yiwei; Zhou, Yi; Yu, Fangning; Li, Xinyi; Zhang, Ning (Frontiers in Pharmacology, 2022)
Diabetic kidney disease (DKD) is the major reason of chronic kidney disease (CKD)-caused end-stage renal failure (ESRF), and leads to high mortality worldwide. At present, the treatment of DKD is mainly focused on controlling the hyperglycemia, proteinuria, and hypertension, but is insufficient on the effective delay of DKD progression. Cordyceps sinensis is a kind of wild-used precious Chinese herb. Its extracts have effects of nephroprotection, hepatoprotection, neuroprotection, and protection against ischemia/reperfusion‐induced injury, as well as anti-inflammatory and anti-oxidant activities. According to the theory of traditional Chinese medicine, cordyceps sinensis can tonify the lung and the kidney. Several Chinese patent medicines produced from cordyceps sinensis are often used to treat DKD and achieved considerable efficacy. This review summarized the clinical usage of cordyceps sinensis, as well as its mainly biological activities including anti-hyperglycemic, anti-inflammatory, immunomodulatory, anti-oxidant, anti-fibrotic activities and regulation of apoptosis.